Pedagogical conditions of managing the development of professional competence of teachers of the New Ukrainian School - Bikova, M.; Protsenko, I. (Problems of Engineer-Pedagogical Education, 2021)
The changes that have taken place in education require modern teachers to actively develop professional competencies. The concept of the New Ukrainian School emphasizes that graduates of education institutions must be individuals, patriots and innovators. The article considers the pedagogical conditions for managing the development of professional competence of teachers of the New Ukrainian School, based on the analysis of scientific-theoretical and methodological literature. The study is based on the vision of managing the development of professional competences of teachers by various modern scientists, and also contains a series of theoretical methods: methods of analysis and generalization of scientific data presented in philosophical, psychological, pedagogical, teaching and instructional sources. In determining the pedagogical conditions for managing the development of professional competence of teachers, we proceeded from the fact that any ideas about the professional competence of teachers are derived and depend on the level of knowledge in public opinion, pedagogical theory and practice of mechanisms and conditions of formation and development human beings; the prevailing ideology in this society about the essence and purpose of the man. The study identified five main pedagogical conditions for effective management of the development of professional competences of teachers of the New Ukrainian School, such as creating conditions for the director and his/her deputy to develop professional competence of teachers: creating conditions for the development of professional competence of teachers; managing the development of professional competence of teachers of the New Ukrainian School; being aware of oneself, and one’s intentions through the prism of the development of one’s professional competences; planning consciously certain individual changes in oneself caused by the needs of teachers’ professional interpersonal communication and cooperation with others; introducing interactive forms of education that provide the teacher with the experience of cognition and critical thinking of practice and learning, education of students according to the relevant cultural patterns and norms of professional activity.